Code of Ethics for the use of AI in Translation - Ruwaiza Sasmita; Tiara Azzahra Marpaung (STIKes Ibnu Sina Ajibarang, 2025)
The development of Artificial Intelligence (AI) has brought significant changes to the field of translation, offering ease and efficiency in the translation process. However, its use raises various ethical issues that need to be regulated through a clear code of ethics. This study discusses the Code of Ethics for the Use of AI in Translation, encompassing key principles such as accountability, transparency, privacy, fairness, and cultural respect.The code of ethics aims to optimize AI's potential while minimizing negative impacts, such as algorithmic bias, loss of cultural meaning in translations, and the declining role of human translators. Through literature reviews and case studies, this research recommends steps such as regular AI system audits, human-AI collaboration, and compliance with data privacy laws. By implementing this code of ethics, the use of AI in translation is expected to operate responsibly, support linguistic diversity, and uphold professional standards in the field of translation.